The Importance of Belt and Road Initiatives for Indonesia in Realizing the Global Maritime Fulcrum - Muhammad Zulham (PUSJIANMAR SESKOAL, 2021)
AbstractThis paper will provide an overview of the importance of the existence of the Belt and Road Initiative for Indonesia which is moving to become the Global Maritime Fulcrum. BRI, which is China's move to become a super power, is considered a stepping stone for Indonesia. The cooperation that has been established with the signing of the MoU from the two countries between GMF and BRI in 2018. This paper uses the concept of national interest which is the reason for BRI as a stepping stone for Indonesia as well as an environmental concept that emphasizes the importance of BRI for Indonesia. In the discussion of this paper, the author first provides an overview of BRI, which is then followed by the Global Maritime Fulcrum. After the two variables are explained, the author provides an overview of the importance of BRI for Indonesia.Keywords: Belt and Road Initiative, Global Maritime Fulcrum